ASSESSMENT OF THE CHALLENGES OF LOGISTICS OF RELIEF MATERIAL AT INTERNALLY DISPLACED PERSONS (IDPS) CAMPS IN NORTH CENTRAL NIGERIA - Ajiboye, Araoye Olarinkoye; Obafemi, Andrew Adesola; Emenike, Gladys C. (African Journal of Social and Behavioural Sciences, 2024)
Aids organisations are scrambling to give relief supplies in a shorter amount of time due to disasters that occur unprepared. Due to difficulties in their logistics system, the rapid demand for relief supplies by catastrophe victims has an impact on how well the humanitarian aid logistics can meet the demand. The purpose of this research is to identify the main challenges that the humanitarian logistics of relief supplies in the IDP camps in North Central Nigeria are facing. The study developed a null hypothesis stating that the six major challenges facing humanitarian logistics of relief supplies across aid organizations are not statistically significant. The IDP camps in Malaysian Garden and Area 1 in Federal Capital Territory were selected for this study using a purposeful sampling method. 120 questionnaires were distributed across the humanitarian relief organisations using convenience sampling. Eighteen challenges that were identified were factored into 6 significant challenges using factor analysis. The data gathered from the humanitarian relief employees was analysed using frequency, percentages, and mean index score while T-Test statistics were used to evaluate the study’s hypotheses. The study’s findings, however, indicate that the major challenges encountered by the aid organisations are inadequate data on the number of disaster victims, inadequate handling infrastructures, inadequate resources to plan the delivery of relief items, poor transport facilities, inadequate staff, and inadequate procurement method during disasters. The study concluded that there is a statistically significant to the 6-major challenges of humanitarian logistics of relief items across the aid organisation. The study therefore recommends among others that adequate resources should be made available by the government to aid organisations in order to plan the delivery exercise.